Análisis comparativo entre los factores determinantes del e-commerce del sector retail en Lima Metropolitana-Perú y Seúl-Corea del Sur - Salcedo Guevara, Claudia Lucia (2022)
This research compares the main factors that affect the development of e-commerce in Lima - Peru in perspective with Seoul - South Korea. For these purposes, the factors of digital competitiveness, consumer profile and financial payment transaction processes were considered, which were measured through indexes, documentary review and a survey with a representative sample of Metropolitan Lima (2020), compared to an existing survey for Seoul (2020). The favourable and facilitating environment for e- commerce adoption and implementation in South Korea was conclusively identified, exhibited in the higher frequency of monthly purchases compared to Metropolitan Lima, the low number of negative experiences in online purchases, and the significant participation 30–50-year-olds in the online shopper segment. The latter exposes the existence of an entrenched digital culture and a consolidated, highly developed market, which in large measure occurs due to the promotion of public policies. Put in contrast, it allows to identify aspects of improvement in Peru for aspects of the legal, digital, and financial process framework.